Comparison of the clinical estimation of cup-to-disk ratio by direct ophthalmoscopy and optical coherence tomography - Amedo, Angela Ofeibea (Ther Adv Ophthalmol, 2019)
OBJECTIVE: To compare the clinical estimation of cup-to-disk ratio determined by direct ophthalmoscopy and optical coherence tomography in glaucoma diagnosis and monitoring. METHODS: A retrospective, cross-sectional study involving a review of 71 optical coherence tomography scans dating from June 2011 to January 2012 at a private imaging lab in Ghana. At the respective referring facilities, only 31 out of the 71 corresponding patient records were successfully reviewed. RESULTS: Majority (54.84%) of the 31 patient records successfully reviewed were women. The mean age was 44.54 ± 16.15 years. Cup-to-disk ratio was grouped into ⩽0.4, >0.4–0.6, >0.6–0.8, and >0.8–1.0 based on direct ophthalmoscopy values. The overall mean cup-to-disk ratio estimated by the optical coherence tomography and direct ophthalmoscopy were 0.72 ± 0.21 and 0.60 ± 0.26, respectively. Overall, there was no statistically significant difference in the mean cup-to-disk ratio estimation by direct ophthalmoscopy and optical coherence tomography [right eye (p = 0.0629); left eye (p = 0.0766)]. There was a statistically significant difference between direct ophthalmoscopy and optical coherence tomography cup-to-disk ratio estimation for values ⩽0.4 [right eye (p = 0.0061); left eye (p = 0.0063)] and values >0.4–0.6 [right eye (p = 0.0243); left eye (p = 0.0498)]. There was no statistically significant difference between conventional direct ophthalmoscopy and optical coherence tomography cup-to-disk ratio estimation for cup-to-disk ratio >0.6. CONCLUSION: We recommend clinicians document which method they use in evaluating optic nerve head parameters. This is to ensure that subsequent clinical decisions are not influenced by an apparent change in these parameters, especially cup-to-disk ratio as different methods might give different values.